PERSEPSI GURU TERHADAP INTEGRASI PELESTARIAN LINGKUNGAN HIDUP DALAM KURIKULUM MUATAN LOKAL BAHASA JAWA - Cantika, Varary Mechwafanitiara; Wahyudin, Dinn (Universitas Muria Kudus, 2024)
The integration of environmental preservation in the local Javanese content curriculum is expected to be able to collaborate two fields of science which will later provide mutual benefits. The aim of this research is to find out and analyze teachers' perceptions of the integration of environmental conservation in the local Javanese curriculum. This research methode uses a quantitative approach with survey methods. The population of this research is Javanese language teachers at middle and high school levels spread across the provinces of East Java, Central Java and Yogyakarta. The sample in this research was 40 teachers taken using accidental sampling technique. The survey in this research used a questionnaire with a Likert scale. The data in this research will be analyzed using descriptive statistics consisting of min, max, mean, standard deviation and variance with the help of SPSS 25. The results of the research show that overall teachers have a positive perception of the integration of environmental conservation in the local Javanese content curriculum. Teachers are aware of the positive benefits that students can experience from this integration. Apart from that, it needs to be emphasized that the choice of learning methods, approaches and assessments must remain adapted to the values and cultural characteristics of Javanese society.